Collaborative online international learning (COIL): an engaging strategy for narrowing learning distances between two continents - Cardoso Catarina; Duarte Clara C.; Silva Erick J.R.; Fardilha Margarida (Türk Biyokimya Dergisi)
Internationalization is a gold standard of higher education institutions ensuring students’ contact with different environments, including different languages and different cultures. Recently, a universal model has emerged: the Collaborative Online International Learning (COIL), a teaching/learning example of internationalization at home highly driven by the COVID-19 pandemic that boosted online interactions. COIL aims to develop intercultural consciousness and collaborative learning environments among students and faculty from different countries.